The SpoIIAA protein of Bacillus subtilis has GTP-binding properties. - Najafi, S M (1996)
SpoIIAA is the first protein of the spoIIA operon. Here we show that SpoIIAA can bind and hydrolyze GTP. The protein also accepts ATP, but with lower affinity. GDP competes poorly for binding of GTP. The GTPase activity of SpoIIAA is within the range found for other GTP-binding proteins.